Current management of pelvic organ prolapse in aging women: EMAS clinical guide. (April 2018) - Giannini, Andrea; Russo, Eleonora; Cano, Antonio; Chedraui, Peter; Goulis, Dimitrios G.; Lambrinoudaki, Irene; Lopes, Patrice; Mishra, Gita; Mueck, Alfred; Rees, Margaret; Senturk, Levent M.; Stevenson, John C.; et al.
Highlights: Nearly 50% of women will develop some form of pelvic organ prolapse (POP). Symptoms and severity of POP increase significantly across the menopausal transition. Systemic and topical estrogens may improve POP-associated symptoms, but is ineffective in its prevention or treatment. Healthcare professionals dealing with menopause should be knowledgeable on POP. Surgical management of POP requires expertise; complex cases need to be managed within multidisciplinary centers. Abstract: Management of pelvic organ prolapse (POP) is a common and challenging task. Nowadays older women are more active than they were in the past, and the development of POP disrupts quality of life and impairs social and personal activities. The menopausal transition is a time of vulnerability, during which many women start experiencing symptoms and signs of POP. The role of hormonal changes or of hormonal therapies in influencing the development or progression of POP has been explored extensively. The management of POP requires considerable clinical skills. Correct diagnosis and characterization of the prolapse and an identification of the individual woman's most bothersome symptoms are the hallmark of appropriate initial management. Therapy is multimodal and often multidisciplinary, and requires a competence in pelvic medicine and surgery. The integration of hormonal, non-hormonal and surgical strategies is important and needs to be adjusted to changing circumstances on an individualized basis. When surgery is required, optimal management requires clinicians who are familiar with the advantages and disadvantages of all the available strategies and who are able to use these strategies in a tailored manner. Complex cases should be sent to specialist referral centers. Management of POP should be integrated into the practice of healthcare professionals dealing in menopause.